Sistem Pengambilan Keputusan Penentuan Lokasi Usaha Salon di Banda Aceh Menggunakan Metode SAW - Sari, Yuliana (Journal Digital Technology Trend, 2024)
This research aims to develop a web-based decision-making system to identify strategic locations for salon businesses in Banda Aceh using the Simple Additive Weighting (SAW) method. The primary issue is the critical need to select an optimal location to minimize business risks, enhance competitiveness, and maximize profits in the service sector, particularly salons, influenced by factors such as accessibility, proximity to crowded areas, competitor presence, female population aged 15–50 years, upper-middle-class population, and rental costs. The methodology includes direct field observations, in-depth interviews with salon owners, and data analysis using SAW based on six key criteria. The system features a user-friendly interface with a main menu and submenus, including data alternatives, criteria, analysis, graphs, reports, and user management, to streamline data input, processing, and visualization. Data were collected through in-person and online questionnaires, processed using PHP and MySQL-based software. The results indicate that Syiah Kuala (Darussalam) achieves the highest score of 0.83, making it the optimal location, presented through ranking tables and bar graphs for clear visualization. The system significantly improves decision-making efficiency and effectiveness by providing accurate location recommendations, assisting both existing and prospective salon entrepreneurs in selecting strategic locations that ensure long-term business success in Banda Aceh.